A reliability study of the rapid emergency triage and treatment system for children. Issue 1 (December 2016) - Henning, Brita; Lydersen, Stian; Døllner, Henrik
Abstract Background To evaluate inter- and intrarater reliability of a new Scandinavian triage system for children, the Rapid Emergency Triage and Treatment System-pediatric (RETTS-p). Methods Two observational studies were conducted at the Pediatric Emergency Department (PED), St. Olav's University Hospital, Trondheim, Norway. Using RETTS-p, nurses assign one of five triage priority levels to each patient on the basis of clinical signs and symptoms evaluations and vital parameter measurements. Study 1: Prior to the introduction of RETTS-p in 2012, all nurses in the PED completed a theoretical and practical training. Four months later, 19 nurses triaged 20 fictive but realistic pediatric cases two times 9 months apart (Waves A and B).Study 2: Nurse pairs consisting of a regular nurse and a research nurse simultaneously and independently triaged 200 pediatric patients who were referred with various common medical and surgical complaints. Results Study 1: Kendall's W for Waves A and B were 0.822 and 0.844, respectively. Using a mixed linear model, we found no difference in triage priority levels between Waves A and B. Compared to a consensus level made by the research group, the nurses rated 85.1 % fictive cases correctly, and 99 % were rated correctly or within one adjacent priority score.Study 2: The interrater correlation coefficient in a linear mixed model was 0.762, confirming a high interrater reliability in real-life triaging. Discussion We found a very high degree of agreement between nurses who used RETTS-p to prioritize children, both in a theoretical case scenarios study, but also in real-life triaging. Conclusions RETTS-p may be a credible and robust triage system, but it has not been validated yet.